Prolonged suppression of HBV in mice by a novel antibody that targets a unique epitope on hepatitis B surface antigen. Issue 4 (30th September 2015) - Zhang, Tian-Ying; Yuan, Quan; Zhao, Jing-Hua; Zhang, Ya-Li; Yuan, Lun-Zhi; Lan, Ying; Lo, Yu-Chieh; Sun, Cheng-Pu; Wu, Chang-Ru; Zhang, Jun-Fang; Zhang, Ying; Cao, Jia-Li; et al.
Abstract : Objective: This study aimed to investigate the therapeutic potential of monoclonal antibody (mAb) against HBV as a novel treatment approach to chronic hepatitis B (CHB) in mouse models. Methods: Therapeutic effects of mAbs against various epitopes on viral surface protein were evaluated in mice mimicking persistent HBV infection. The immunological mechanisms of mAb-mediated viral clearance were systematically investigated. Results: Among 11 tested mAbs, a novel mAb E6F6 exhibited the most striking therapeutic effects in several HBV-persistent mice. Single-dose administration of E6F6 could profoundly suppress the levels of hepatitis B surface antigen (HBsAg) and HBV DNA for several weeks in HBV-transgenic mice. E6F6 regimen efficiently prevented initial HBV infection, and reduced viral dissemination from infected hepatocytes in human-liver-chimeric mice. E6F6-based immunotherapy facilitated the restoration of anti-HBV T-cell response in hydrodynamic injection (HDI)-based HBV carrier mice. Immunological analyses suggested that the Fcγ receptor-dependent phagocytosis plays a predominant role in E6F6-mediated viral suppression. Molecular analyses suggested that E6F6 recognises an evolutionarily conserved epitope (GPCK(R)TCT) and only forms a smaller antibody–viral particle immune complex with limited interparticle crosslinking when it binds to viral particles. This unique binding characteristic of E6F6 to HBV was possibly associated with its effective in vivo opsonophagocytosis for viral clearance. Conclusions: These results provided new insight into understanding the therapeutic role and mechanism of antibody against persistent viral infection. The E6F6-like mAbs may provide a novel immunotherapeutic agent against human chronic HBV infection.